Bilimsel çalışmaları ve danışmanlığını uaptığı lisansüstü çalışmalar örneğinde Prof. Dr. Mehmet Orhan Okay’ın bilim insanı portresi - GÜNEŞ, MEHMET (My University, 2020)
Orhan Okay, sadece Yeni Türk Edebiyatı sahasının değil Türk akademisinin en üretken bilim insanlarından biridir. Akademik hayata adım attıktan sonra alandaki önemli eksiklikleri kapatacak oldukça özgün ve nitelikli çalışmalar yapmıştır. Yeni Türk Edebiyatı sahasında birçok lisansüstü çalışmalara danışmanlık yaptığı gibi, birçok bilimsel çalışmaya da gönüllü destek vermiştir. Bu çalışmada Prof. Dr. Orhan Okay’ın bilimsel yayınlarından ve danışmanlığını yaptığı lisansüstü çalışmalar örneğinde, bilim insanı portresi tespit edilmektedir

Orhan Okay is one of the most prolific academics not only in the field of Modern Turkish Literature but also in the Turkish academy. After stepping into academic life, he has done very original and qualified works to fill the gap in the field. As well as working as a supervisor for many postgraduate studies in the field of modern Turkish literature, he has also voluntarily supported many academic studies. In this study, the portrait of a scientist has be determined within the scope of Prof. Dr. Orhan Okay’s academic studies and graduate studies he supervised.
Prof. Dr. Mehmet Orhan Okay’s potrait as an academic within the scope of his academic studies and graduate studies he supervised
Keywords: Orhan Okay; Yeni Türk Edebiyatı; bilimsel yayınlar; bilim insanı portresi; Modern Turkish Literature; academic publications; portrait of a scientist